Pengaruh Academic Burnout dan Motivasi Belajar Terhadap Prestasi Akademik SMA Negeri 4 Sidoarjo - Rizky Nur Amaliyah; Eka Indah Nurlaili (Journal of Innovative and Creativity, 2025)
This study aims to determine the effect of academic burnout and learning motivation on the learning achievement of 10th-grade students in economics at SMA Negeri 4 Sidoarjo. This study involved 206 respondents from 10th-grade students taking economics. Data collection was conducted through the distribution of questionnaires using Google Forms. Data analysis was conducted using Statistical Package for the Social Sciences (SPSS) software. Based on the analysis results, it was found that academic burnout has a negative and significant effect on student learning achievement. This means that the higher the level of academic burnout experienced by students, the lower their learning achievement. Conversely, learning motivation has a positive and significant effect on student learning achievement. The higher the learning motivation of students, the better their learning achievement in economics. This finding indicates the importance of efforts to reduce academic burnout and increase learning motivation in order to support student academic achievement. Therefore, schools and teachers are expected to create a conducive learning environment and provide emotional and academic support to prevent burnout and optimally encourage students' enthusiasm for learning.